Effectiveness of early intervention and combination treatment with monoclonal antibodies and antivirals in oncohematological patients with SARS-CoV-2: a retrospective experience - Di Bari, Silvia; Izzo, Francesco; Bresciani, Livia; Mancarella, Giulia; Garattini, Silvia; Gasperin, Andrea; Di Trento, Daniela; Grimaldi, Alessandra; Parente, Alberico; Marocco, Raffaella; Carraro, Anna; Kertusha, Blerta; et al. (Frontiers in Immunology, 2025)
Patients with acute SARS-CoV-2 and pre-existing oncohematological conditions challenge clinicians due to a heightened risk for severe COVID-19 and forced deferral of cancer treatment. Different treatment approaches aim to either prevent the progression of mild disease (“early therapy”) or to treat more severe COVID-19. Currently, there is limited evidence supporting the effectiveness of a tailored approach for oncohematological patients. We present a real-world experience from two university hospitals. In this retrospective study we recruited oncohematological patients hospitalized for SARS-CoV-2 pneumonia between March 2020 and June 2023 from two hospitals in Latium, Italy. Patients with COVID-19 pneumonia received either antiviral or monoclonal antibodies (MoAb) alone, a dual therapy (antiviral with MoAb) or a triple therapy (two different antivirals and MoAb). The study aimed to evaluate the practical management of hospitalized oncohematological patients with COVID-19. We focused on the impact in patients with COVID-19 related pneumonia of specific therapies, early treatment, and tixagevimab-cilgavimab prophylaxis on in-hospital mortality and viral clearance time. Overall, 101 patients were recruited, 76 (75.24%) patients developed pneumonia, and 16 (15.84%) patients died from any cause. While most patients (75,25%) did not receive “early therapy”, those who did had a higher chance of survival (p=0.04). Furthermore, the pneumonia subgroup treated with early therapy demonstrated a higher survival rate as well (p=0.02). Out of the hospitalized patients triple therapy resulted in lower mortality (all patients survive in this group). This group also showed a significant reduction in the time to viral clearance from the first day of the evaluated therapy (6 days [IQR 4;9]), compared to patients treated with only remdesivir (17 days [IQR 8;37]) (p=0.03). Our findings demonstrate that early therapy significantly reduces in-hospital mortality, while triple therapy accelerates viral clearance in hospitalized patients. These results, in line with recent studies, underscore the critical importance of prompt treatment and a multitargeted pharmacological approach for optimizing outcomes in oncohematological patients with SARS-CoV-2. Future research, involving larger cohorts, should delve deeper into COVID-19 treatment strategies for this vulnerable population, with a particular emphasis on the elderly, who continue to experience high mortality rates.